Identification Of Bioactive Peptide From Chicken Ovalbumin Using An Integrated Bioinformatics-assisted Approach And Determining Their Functional Significance - Mohd Salim, Mohd Adam (2021)
complete integrated bioinformatics approach was developed to identify angiotensin-converting enzyme (ACE) and dipeptidyl peptidase-4 (DPP-4) inhibitory peptides from chicken ovalbumin (OVA). This approach involved PeptideCutter, Peptide Ranker and Pepsite2 in order to hydrolyse OVA protein sequence into smaller peptides, to identify the probability of the peptides being bioactive and to investigate the interaction between the peptides and target enzymes (i.e. ACE and DPP-4), respectively. OVA sequence was initially hydrolysed using PeptideCutter. Pepsin (P), Chymotrypsin (C) and Trypsin (T) were used in 7 different OVA (O) hydrolysis combination (OP, OC, OT, OCT, OPC, OPT and OPCT), thus, producing 71 peptides. Top ten novel bioactive peptides (i.e. CF, KM, ELPF, AM, ADHPH, LPR, PR, FR, PRM and GR) were then successfully identified and selected based on the amino acid sequences as well as the peptide interactions with ACE and DPP-4. Against ACE, IC50 of CF, KM, ELPF, AM, ADHPH, LPR, PR, FR, PRM and GR were 1.82, 1.89, 4.24, 3.07, 3.54, 1.30, 5.47, 4.35, 5.22 and 3.11 mM, respectively. These results were comparable to commercial inhibitor for ACE, captopril (IC50 = 3.98 mM). While against DPP-4, however, inhibitory activities were only comparable to other reported DPP-4 inhibitory peptides such as EK (IC50 = 3.22 mM) and GL (IC50 = 2.62 mM), as the peptides were able to achieve 2.99, 2.22, 9.92, 2.79, 1.66, 1.43, 4.11, 2.47, 2.50 and 2.83 mM, respectively